Bullying and Academic Performance: A Study of Selected Secondary Schools in Lagos, Nigeria - Victoria Agboola Oluwamumibori; Christiana Adetunde; George Tayo Ola; David Imhonopi; Matthew Egharevba; Ajibade Jegede; Mofoluwake Ajayi (Richtmann Publishing, 2022)
Bullying is inappropriate behaviour that children and adolescents face daily in schools all around the world. It is prevalent in today's schools and is commonly found in secondary schools. It is a complicated social problem that can have serious negative implications for both bullies and victims, especially when the victim is physically or psychologically harmed. Therefore, the study examines bullying and academic performance, in a study of selected secondary school students in Alimosho local government area, Lagos, Nigeria. A survey method was utilized using the structured questionnaire as an instrument of data collection. Utilizing a multi-stage random sampling, three hundred and fifty questionnaires were administered to students in the four secondary schools. Quantitative data were analyzed utilizing the descriptive statistics with the aid of the Statistical Package for Social Science (SPSS) version 23. The analysis of the questionnaire was based on descriptive analysis with the use of frequency counts and percentages. The study’s findings show a negative relationship between bullying and students’ academic performance. Result also shows that addiction to alcohol and loss of concentration is the major effect of bullying on students’ academic performance. This study recommends that teaching empathy and encouraging victims to make timely reports on the incidence of bullying are crucial to mitigating bullying and its consequences in secondary schools in Lagos state. Received: 11 July 2022 / Accepted: 27 August 2022 / Published: 2 September 2022